Les listes de proscriptions au temps de la Ligue - Marco Penzi (Mélanges de la Casa de Velázquez, 2014)
The history of the Catholic League is one of compilation of lists—like the list of proscripts created in March 1594 following Henry IV’s entry to Paris; or the papier rouge, a list of the Politiques of whom the Sixteen of Paris wished to rid the city in 1591 following the assassination of President Brisson. Henry IV’s policy tended to be moderate in its treatment of former League members, and likewise of the expelled, but nonetheless we shall find that the Politiques who won the war used this 1594 list to brand the outcast Leaguers forever as villains.